2016
DOI: 10.3390/ijgi5110194
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Precipitation Regime in China from 1961 to 2014 from the Standardized Precipitation Index

Abstract: Prediction of drought and flood events can be difficult, but the standardized precipitation index (SPI) calculated from monthly data may be a useful tool for predicting future dryness/wetness events in China. The rainy season SPI was calculated from monthly precipitation data from 3804 meteorological stations in China. The spatiotemporal variation, periodic change, and trend in rainy season SPI from 1961 to 2014 in eight regions were investigated. The results indicate that the rainy season SPI is valuable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The results from this study showed that Rs decreased from east to west and from south to north in China. A possible reason for the east‐to‐west gradient is the fact that Pm in China, which is positively correlated with Rs (Table S1; Yuan et al, 2016), decreases from east to west. Also, a possible reason for the south‐to‐north gradient may be linked to the spatial patterns of Pm and Tm in China, which are much higher in the south than in the north.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from this study showed that Rs decreased from east to west and from south to north in China. A possible reason for the east‐to‐west gradient is the fact that Pm in China, which is positively correlated with Rs (Table S1; Yuan et al, 2016), decreases from east to west. Also, a possible reason for the south‐to‐north gradient may be linked to the spatial patterns of Pm and Tm in China, which are much higher in the south than in the north.…”
Section: Discussionmentioning
confidence: 99%
“…When given a significant level of α = 0.05, | τ | ≥ 0.184 indicates a significant trend. More details on the Mann‐Kendall nonparametric correlation test can be found in Yuan, Jian, and Jiang (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The temperature of colder regions is increasing at higher rate compared to the rest of the globe, and almost 1,700 Pg of organic carbon is stored in the permafrost (Tarnocai et al, 2009). However, substantial uncertainty still exists in the response of primary productivity to CO 2 fertilization (Korner et al, 2005;Norby et al, 2005Norby et al, , 2010 and global warming induced drought at regional and global scales (Yuan et al, 2016;Zhao & Running, 2010). Given the larger increases in rate observed in this study, the loss of soil carbon stocks may be towards the upper end (around 200 Pg C) of the uncertainty bounds if human emissions are not limited , mainly driven by carbon losses in colder climates.…”
Section: 1029/2018ef000937mentioning
confidence: 99%
“…An increase in primary production carbon may offset losses from soil respiration, as a recent study found that the rate of net biome productivity (which is the difference between net primary production and autotrophic respiration) has significantly accelerated during the warming hiatus Ballantyne et al, 2017). However, substantial uncertainty still exists in the response of primary productivity to CO 2 fertilization (Korner et al, 2005;Norby et al, 2005Norby et al, , 2010 and global warming induced drought at regional and global scales (Yuan et al, 2016;Zhao & Running, 2010).…”
Section: 1029/2018ef000937mentioning
confidence: 99%
“…There is no unified standard for the definition of CDHEs, because drought events and heatwave events correspond to a variety of definitions. Drought events are usually defined by various indicators, such as the standardized precipitation index (SPI) [8,9], the standardized precipitation evapotranspiration index [10,11], and the Palmer drought severity index [12,13]. Heatwave events are mainly defined by relative thresholds (percentile thresholds), absolute thresholds, and durations [14,15].…”
Section: Introductionmentioning
confidence: 99%